Justice and Reconciliation as Social Recognition: A Reading from The Spirit of Christianity and Its Fate of Hegel and Its Update in Axel Honneth - Feiler, Adilson Felicio (Revista Ágora Filosófica, 2018)
Our research reflects on the passing of a justice model linked to moral law imputes, positive punishment for non-compliance, for a model that reconciles justice. Following this line of thought, we add the contributions of Axel Honneth, according to which the establishment of a normative principle of justice must provide guidance for political action. This was only made possible to the extent that such principles are allied to social practices. By analyzing the Spirit of Christianity and its Fate, an early work of Hegel, we intend to verify the relevance of the concept of justice, for the design of the hegelian attack on the positive law and subsequent defense of ethics as reconciliation and fullness of life. From the understanding of justice as reconciliation in Hegel we approach that which underlies the reconstruction of social practices as Honneth understands.